Kearifan Lokal dalam Sastra Indonesia sebagai Media Pendidikan Karakter - Anita Candra Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Indonesian literature is one of the effective media in instilling local wisdom values ​​and character education. Various literary works such as folk tales, legends, fables, and novels are full of moral values ​​that can shape the personality of their readers. This article aims to examine how local wisdom contained in Indonesian literature can be a means of character education for the younger generation. The method used in this study is a literature study by analyzing various references related to local wisdom in literature and its relevance to character education. The results of the study show that Indonesian literature not only functions as entertainment, but also as a learning medium that can instill character values ​​such as honesty, hard work, tolerance, and love for the homeland. Thus, the use of literature in education needs to be increased so that the younger generation increasingly recognizes and internalizes local wisdom values.